Unhealthy Housing - Burridge, R. (Taylor & Francis, 1993)
Unhealthy Housing presents an analysis of the research into the health implications of housing and the significance for legal regulation of housing conditions. Key experts present short papers, together with an overview to give an evaluation of the significance of housing on the health of occupiers.